Cellular senescence in tumor immune escape: Mechanisms, implications, and therapeutic potential - You, Li; Wu, Qinghua (Critical reviews in oncology/hematology, 2025)
Cellular senescence, a hallmark of aging, has emerged as a captivating area of research in tumor immunology with profound implications for cancer prevention and treatment. In the tumor microenvironment, senescent cells exhibit a dual role, simultaneously hindering tumor development through collaboration with immune cells and evading immune cell attacks by upregulating immunoinhibitory proteins. However, the intricate immune escape mechanism of cellular senescence in the tumor microenvironment remains a subject of intense investigation. Chronic inflammation is exacerbated by cellular senescence through the upregulation of pro-inflammatory factors such as interleukin-1β, thereby augmenting the risk of tumorigenesis. Additionally, the interplay between autophagy and cellular senescence adds another layer of complexity. Autophagy, known to slow down the aging process by reducing p53/p21 levels, may be downregulated by cellular senescence. To harness the therapeutic potential of cellular senescence, targeting its immunological aspects has gained significant attention. Strategies such as immune checkpoint inhibitors and T-cell senescence inhibition are being explored in the context of cellular senescence immunotherapy. In this comprehensive review, we provide a compelling overview of the regulation of cellular senescence and delve into the influencing factors, including chronic inflammation, autophagy, and circadian rhythms, associated with senescence in the tumor microenvironment. We specifically focus on unraveling the enigmatic dual role of cellular senescence in tumor immune escape. By deciphering the intricate nature of cellular senescence in the tumor microenvironment, this review aims to advance our understanding and pave the way for leveraging senescence as a promising target for tumor immunotherapy applications. [Display omitted] •Understanding the mechanism of cellular senescence and tumor immune escape leads to better tumor therapy.•Cellular senescence plays a dual role in tumor immune escape.•Chronic inflammation and autophagy, are linked to cellular senescence.•Circadian rhythms regulate cellular senescence, which is associated with tumor immune escape.•Targeting cellular senescence in immunotherapy is a promising approach in cancer treatment.